Clinical practice of precision medicine in lymphoma. Issue 2 (19th May 2022) - Ji, Lili; Hua, Fanli; Wu, Yu; Qiao, Tiankui; Gu, Jianying; Zhang, Xiaohui; Liu, Peng; Li, Feng; Cheng, Yunfeng
Abstract : Background: Lymphoma is the most common malignancy in blood system. There are still unmet treatment needs in Hodgkin's and non‐Hodgkin's lymphoma. Materials & Methods: We searched reviews and clinical trials on genetic medicine of lymphoma in Pubmed, the prevelance of lymphoma in Pubmed as well as SEER. Results: Genetic analysis helps the practice in lymphoma. For some molecules have become diagnostic markers in some subtypes of lymphoma. Some genetic disorder could forecast the prognosis. Besides, new target drug could be chosen as individual treatment according to the genetic changes in lymphoma cells. Conclusion: Precision medicine has shown promising future in the field of lymphoma. Abstract : In ITP, Treg cells play an important role in pathogenesis. Treg cells decrease as their output from thymus decreased and their plasticity in peripheral blood. Meanwhile, Treg cells' function impaired. New treatment may develop focusing on the abnormality of Treg cells.